New records of Decapod Crustaceans (Decapoda: Pontoniinae and Inachidae) associated with sea anemones in Turkish waters - DURIS, Z.; ATES, A. S.; OZALP, H. B.; KATAGAN, T. (Mediterranean Marine Science, 2013)
Three anemone-associated decapod crustaceans, two shrimp species, Periclimenes amethysteus and P. aegylios (Caridea: Palaemonidae: Pontoniinae), and the crab Inachus phalangium (Brachyura: Inachidae), all collected from the Dardanelles, are reported for the first time from Turkish coasts. Another inachid crab, Macropodia czernjawskii is also reported for the first time to occur in association with the sea anemone, Anemonia viridis. Periclimenes scriptus was the fifth decapod species recorded associated with sea anemones within the present study, and while this species has already been reported from Turkish waters, this is the first time it is recorded from the Dardanelles (the Turkish Straits System).